KARAKTERISASI POLIMER BAHAN ADESIF UNTUK KULIT DAN PLASTIK - Roestamsjah Roestamsjah; Nuri Astrini (Research Center for Chemistry - LIPI, 1993)
Characterization of polymer of five commercially available elastomeric adhesives claimed 'suitable for leather and plastics had been conducted. Polymer samples were isolated from adhesive solutions by precipitation, and then characterized through FTIR spectroscopy, viscometry, GPC and thermal analysis. The FTIR spectrogram, indicate that five different samples of adhesives contained polychloroprene. Thermal analysis indicated similar glass transition points (Tg) of -40 to -43°C and three of them indicated the second glass transitions at 1.4; 3.6 and 13.5°C, Five adhesives indicated melting points (Tm) of polymers at 43 - 48°C, The average viscosity molecular weight (Mv) indicated two groups; i.e. Mv: 115,000 - 146,000 and Mv : 357,000 - 425,000. From secondary sources, polychloroprene has solubility parameter 8= 8.2 - 9.4 (cal em -3)0.5 or 16.74 - 19.13 (kJ m-3)0.5 and critical surface tension Yc = 38 dyne cmr-1 or mN m-1.